Influence of aggregate sizes and packing combination on the properties of pervious concrete - Arcolezi, Karina Hwang (2022)
Pervious concrete is a construction material that can be used as a pervious pavement and appears as a potential mitigator of floods and other problems related to soil waterproofing. Developing an efficient pervious concrete is crucial to promote its use on a large scale. This study aims to evaluate the effect of basaltic aggregates packing throughout maximum density methodology on the properties of pervious concrete. To this end, an experimental program related to using maximum density methodology for packing aggregates is presented to improve the mechanical properties of pervious concrete. The pervious concrete was produced using three different aggregates granulometry and their combinations using the packing with the maximum density methodology. The pervious concrete's physical, mechanical and hydraulic properties were determined for concretes after 28 days of curing, yielding up to 18 MPa in compressive strength with porosities varying between 25 and 35% and without significantly impairing the permeability of the pervious concrete. A multiple regression model was carried out for statistical analysis of the results. The results indicate that the compressive strength is significantly more influenced by the density and size of the aggregate. In contrast, the impact resistance was influenced by all parameters (density, porosity, and aggregate size). Thus, in addition to the improved properties demonstrated, the use of pervious concrete can also reduce the environmental problems associated with flooding from rainwater on pavements, contributing to sustainable development.